Association of dietary cholesterol and dyslipidemia in Chinese health examinees - Junqiang Pan; Wenqi Han; Yongrong Jiang; Jine Wu; Xin Zhou (BMC, 2022)
Abstract Background The association between dietary cholesterol consumption and dyslipidemia is still in controversy. The study aims to evaluate whether dietary cholesterol intake associated with dyslipidemia and its components in Chinese health examinees. Methods A large-scale cross-sectional study was conducted among health examinees of in Shaanxi province. Totally of 8358 participants (3677 male and 4681 female) were included. Dietary cholesterol intake was assessed by validated food frequency questionnaire. Multivariable regression and restricted cubic spline models were used to capture the linear and non-linear association between dietary cholesterol and dyslipidemia. Results A total of 2429 (29.1%) subjects were newly diagnosed of dyslipidemia, the prevalence was 29.2% in male and 27.7% in female. Mean intake of dietary cholesterol was 213.7 mg/day. After adjusting for all potential confounders including demographics information and lifestyles, higher cholesterol consumption was related to lower risk of dyslipidemia, the ORs (95% CIs) across Q2 to Q4 group were 0.87 (0.60-1.26), 0.80 (0.55-1.18) and 0.61 (0.41-0.91) in female. With further controlling for nutrients principal components, a null association was observed between dietary cholesterol and dyslipidemia and serum lipids, regardless of gender. Results of restricted cubic splines showed that the risk of dyslipidemia decreased slowly until around 300 mg/day in men and 200 mg/day in women, although the non-linear association was not significant. Conclusions The study suggested that dietary cholesterol consumption was not associated with dyslipidemia or serum lipids in Chinese health examinees, although a decreased risk was observed before the threshold points.